So close, so different: geothermal flux shapes divergent soil microbial communities at neighbouring sites. Issue 2 (12th November 2015) - Gagliano, A. L.; Tagliavia, M.; D'Alessandro, W.; Franzetti, A.; Parello, F.; Quatrini, P.
Abstract: This study is focused on the (micro)biogeochemical features of two close geothermal sites (FAV1 and FAV2), both selected at the main exhalative area of Pantelleria Island, Italy. A previous biogeochemical survey revealed high CH4 consumption and the presence of a diverse community of methanotrophs at FAV2 site, whereas the close site FAV1 was apparently devoid of methanotrophs and recorded no CH4 consumption. Next‐Generation Sequencing (NGS) techniques were applied to describe the bacterial and archaeal communities which have been linked to the physicochemical conditions and the geothermal sources of energy available at the two sites. Both sites are dominated by Bacteria and host a negligible component of ammonia‐oxidizing Archaea (phylum Thaumarchaeota). The FAV2 bacterial community is characterized by an extraordinary diversity of methanotrophs, with 40% of the sequences assigned to Methylocaldum, Methylobacter (Gammaproteobacteria) and Bejerickia (Alphaproteobacteria); conversely, a community of thermo‐acidophilic chemolithotrophs ( Acidithiobacillus, Nitrosococcus ) or putative chemolithotrophs ( Ktedonobacter ) dominates the FAV1 community, in the absence of methanotrophs. Since physical andchemical factors of FAV1, such as temperature and pH, cannot be considered limiting for methanotrophy, it is hypothesized that the main limiting factor for methanotrophs could be high NH4 + concentration. At the same time, abundant availability of NH4 + and other high energy electron donors and acceptors determined by the hydrothermal flux in this site create more energetically favourable conditions for chemolithotrophs that outcompete methanotrophs in non‐nitrogen‐limited soils.